PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN PERPINDAHAN KALOR DI SEKITAR KITA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS V SD INPRES OEBA 1 KOTA KUPANG - Anggos, Maria Suryanti; Selly, Jannes Bastian; Koro, Maxsel (SINERGI : Jurnal Riset Ilmiah, 2025)
The objective of this study is to improve students' learning outcomes in understanding heat transfer in our surroundings through the implementation of the Problem Based Learning (PBL) model. This research is a Classroom Action Research (CAR) conducted in two cycles. The PBL model was chosen because it is believed to encourage students to think critically, be active, and discover concepts through contextual problem-solving. This approach is expected to help students more easily grasp the abstract concept of heat transfer through meaningful learning experiences.The results of the study showed a significant improvement in student learning outcomes. The percentage of students who met the Minimum Competency Criteria (KKM) increased from 59% in the first cycle to 88% in the second cycle. In conclusion, the application of the Problem Based Learning model is effective in enhancing students’ understanding of heat transfer concepts and can be considered an effective science learning strategy at the elementary school level.